Influence of pain duration and severity on oral health-related quality of life and patient satisfaction during adult treatment with clear aligners - Waleska Caldas; Fabiana Aparecida Bonin; Camila Pereira Vianna; Roberto Hideo Shimizu; Larissa Carvalho Trojan (SpringerOpen, 2024)
Abstract Background This study aims to compare the impact of pain on quality of life and patient satisfaction during treatment with aligners. Methods Ninety-four subjects in active treatment were invited to answer self-reported questions concerning pain severity and duration, occurrence of other signs and symptoms, and level of satisfaction with their treatment. Also, the OHIP-14 questionnaire was applied to assess patients' OHRQoL. Results Ninety-four patients (49 women and 45 men) answered the survey. Pain duration of 1-3 days was reported by 69.1% of patients (n = 60). For those who reported pain (n = 84), it was considered mild severity by 42.9% and moderate by 52.4%. Almost sixty-four percent of the sample were very satisfied with the aligner's aesthetics (n = 60) and forty-nine percent were satisfied with treatment in general (n = 46). Mean OHIP-14 score was 3.36 ± 2.54. OHRQoL was significantly associated with pain severity, whereas patients who reported having experienced moderate pain presented a significantly higher mean OHIP-14 score than those who reported having experienced mild pain (3.92 ± 1.93 and 2.69 ± 2.83, respectively; p = 0.036). The "psychological discomfort" OHIP-14's domain was the most influenced by the level of pain. Conclusion Pain severity significantly influenced OHRQoL, in adult patients under treatment with clear aligners. However, high levels of patient satisfaction were reported, regardless of pain duration or severity.